PERAN MEDIA SOSIAL, USER INTERFACE, DAN CRM TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP DI BALI - Pande Ketut Ribek; Anak Agung Putu Agung; Ni Kadek Desi Mirayani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2025)
Purchase decisions are a process taken by consumers when they get satisfaction. The use of technology makes it very easy for people to get information about purchases using e-commerce in online shops. This study aims to determine the role of social media, user interface and CRM in making purchase decisions in online shops. Quantitative method with a population of people who shop using technology in online shops with purposive sampling. Multiple linear regression analysis analysis technique. The results of the study found that social media has a positive and significant effect on purchase decisions in online shops, User interface has a positive and significant effect on purchase decisions in online shops, and CRM has a positive and significant effect on purchase decisions in online shops. This means that the better the use of social media, user interface and CRM, the better the purchasing decision on online shops in Bali.